Why do individualized curricular adaptations have a bad reputation? The two extremes of the same proposal/answer (Journal of Parents and Teachers, 2014)
The LOGSE opts for a comprehensive school that adapts to the context and caters to all its students, to arbitrate positive discrimination measures in response to special educational needs; in this way, all students are able to learn how to learn. Individualized curricular adaptation (ICA) is seen as a measure that will make it possible to introduce changes to facilitate the personalization of teaching. It is important to ask why and for what purpose the ICA is elaborated, especially to understand what it means for the educational team, in order to be able to elaborate a joint document.
Keywords: ICA; school; education; teachers; positive discrimination; LOGSE